Utilization of Azadirachta indica biodiesel, ethanol and diesel blends for diesel engine applications with engine emission profile. (1st July 2022) - Sathish, T.; Mohanavel, V.; Arunkumar, M.; Rajan, K.; Soudagar, Manzoore Elahi M.; Mujtaba, M.A.; Salmen, Saleh H.; Al Obaid, Sami; Fayaz, H.; Sivakumar, S.
Highlights: BTE increases by 15% for D80B20 blend compared to B100 fuel. Smoke intensity reduces by 29.5% for D80B20 compared to D100. UHC emissions reduces by 34.15% for B100 compared to D100. NOx emission increases by 3.65% for D80B20 compared to D100. D60B20E20 usage will reduce the 40% of the diesel need. HRR and Peak Pressure increases for D60B20E20 fuel blends. Abstract: Plant-based oils have the most important role in the biodiesel research in engines used for different applications like automobiles, marines, fishing boats, power generators and others. Thisstudy deals with the non-edible plant-based oil of Azadirachta indica, (locally knows as neem), ethanol and diesel fuels for the IC engine. There are three blending D80B20 (80% of diesel and 20% of bio-fuel of Azadirachta indica oil), B80E20 (80% of diesel and 20% of ethanol) and D60B20E20 (60% of diesel, 20% of bio-fuel of Azadirachta indica oil & 20% ethanol) were created for the comparison with 100 % of diesel and 100% of Bio-fuel of Azadirachta indica oil. The brake thermal efficiency (BTE) and emissions such as smoke, carbon-monoxide (CO), hydrocarbons (HC) and nitrogen oxides (NOx) of exhaust also examined for the comparison. All the values gained by the experiments were clearly compared and the corresponding variations in percentage with diesel fuel are spotlighted. The proposed fuels D80B20, D60B20E20, and B80E20 exhibits 8.49%, 4.25% and 3.02% higher BTE than pure diesel. B80E20 have the very less CO and smoke index, D80B20 yielded much higher BTE and the low HC when compared with other individual and blend fuels for this investigation. Bio-fuel of Azadirachta indica oil and ethanol combination also exhibited appreciable performance not only in BTE but also in reduction of exhaust emissions Like HC, CO and Smoke intensity than conventional diesel fuel. Hence these blends of biodiesel are recommended using as alternate fuel in IC engine for the engine.